2016
DOI: 10.1007/s10936-016-9438-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bengali Audio–Visual Test Battery for Assessment of Pragmatic Skills: Preliminary Normative Data Based on Educational Level

Abstract: Pragmatic competence may be disrupted due to psychological and neurological causes. For appropriate remedy and rehabilitation, a precise assessment of pragmatic skills is important. However, there is no test battery in the Bengali language, and consequently, there is no published data on pragmatic ability of Bengali speakers. Due to the vast diversity of the population, it becomes increasingly difficult to assess pragmatic ability of an individual without a proper knowledge of the normal variations. To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…A recent study 131 Moreover, "open-ended questions and a naturalistic method of elicitation (verbal explanation) make the battery an ideal tool to explore the diverse minds of a diverse population." 132 Preliminary data suggest that the test battery holds promise for a transdiagnostic approach toward pragmatic deficits across clinical populations. 134 Adaptation of such test batteries might help create a relatively homogenous data set for researchers to better understand the nature of language breakdown in different types of clinical populations, in general, and dementia, in particular, as well as its cultural and language-specific variations.…”
Section: Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study 131 Moreover, "open-ended questions and a naturalistic method of elicitation (verbal explanation) make the battery an ideal tool to explore the diverse minds of a diverse population." 132 Preliminary data suggest that the test battery holds promise for a transdiagnostic approach toward pragmatic deficits across clinical populations. 134 Adaptation of such test batteries might help create a relatively homogenous data set for researchers to better understand the nature of language breakdown in different types of clinical populations, in general, and dementia, in particular, as well as its cultural and language-specific variations.…”
Section: Future Directionmentioning
confidence: 99%
“…figurative language test. The result emphasizes the need for further investigations into the scope of using figurative language tests for detecting individuals with cognitive decline, which could be missed if we rely too much on traditional screening measures.Comprehensive test batteries like the "Bengali Audio-Visual TestBattery for the Assessment of Pragmatic Skills"132 and "Assessment of Pragmatic Abilities and Cognitive Substrates (APACS)" 133 might prove to be helpful. Adapted versions of these comprehensive tests might be advantageous for generating comparable data sets across different languages and cultures.…”
mentioning
confidence: 99%
“…A study by Chakrabarty et al (20) suggested that education is an important variable that interferes with individuals' pragmatic abilities. Another study (21) found that children with learning difficulties presented lower scores than children of typical development in a test that investigates pragmatic abilities, mainly regarding the amount of speech acts, inadequate maintenance of the topic, change of shift, limitation of strategies for repairing communicative breaks, and coherence and cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…implicated the left hemisphere (frontal and parietal lobes) for verbal working memory and the RH (frontal and temporal cortices) for spatial working memory (Nagel et al., 2013). Attention is also intricately intertwined with cognition and consciousness (Chakrabarty et al., 2017) and its deficit can disrupt pragmatic processing. Redcay and Saxe (2013) define joint attention as ‘the act of two people intentionally coordinating their attention on the same thing’.…”
Section: Introductionmentioning
confidence: 99%